(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the expression of diminutive meanings as part of anthroponyms in different systems languages. Our research consists of researching several problems, the linguistic and extralinguistic factors of twins’ names in the form of a linguocognitive phenomenon. Problems associated with extralinguistic features of names are one of the little-studied phenomena in linguistics, and as a result of the analysis it was concluded that the process of naming twins adequately reflects the different formation of each nation, depending on the national characteristics of native speakers.